Competitive Strategy Analysis of Electronic Retail On E-Commerce Shopee (Thomas Electronics Case Study) - Rila Putri Lesmana; Arnis Budi Susanto; Intan Nurul Awwaliyah (International Journal of Economics Accounting and Management, 2026)
This study aims to analyze the competitive strategy of electronic retail on e-commerce Shopee (Thomas Electronics case study). The design of this study uses Mixed-Method. The method used is Sequential Explanatory which combines data from one method with another. The object of research needed is an electronic retail business company in Jember Regency, East Java Province, namely Thomas Electronics for approximately 4 (four) months. Determination of informants in this study was carried out using a purposive approach. This study will use primary and secondary data. The processing of this data is entered to develop a strategy to build loyalty through service quality in the electronic retail business with a strategic management concept approach. Qualitative analysis uses SWOT analysis and Quantitative Strategic Planning Matrix. Based on the discussion analysis, the conclusions are: 1) Based on the SWOT Matrix analysis, the internal factors of Shopee Thomas Electronics consist of the strengths and weaknesses of Shopee Thomas Electronics. Furthermore, the external factors of Shopee Thomas Electronics consist of opportunity and threat factors; 2) After going through data input, matching, and decision stages in the QSPM analysis, the main strategy that gets the highest attractiveness value (6.518) in the QSPM is obtained; 3) The planning of the development of the Shopee Thomas Electronics business model in facing business competition is based on the strategy with the highest priority, namely carrying out flash sale activities at certain moments